The Creative Turn in Arts Scholarship (Sound Stage Screen, 2023)
Edited by Giorgio Biancorosso and Emilio Sala.Contributions by Gillian Anderson, Steven Feld, Michal Grover-Friedlander, Yuichi Kinoshita, Rina Tanaka, Yao Chen, and Judith Zeitlin.